A gangue-based porous magnetic composite material and its preparation method and application

By using porous magnetic composite materials with metal oxide loaded by coal gangue base, the problems of weak magnetic properties and small specific surface area in microplastic removal are solved, and efficient removal of microplastics in wastewater are achieved.

CN119140059BActive Publication Date: 2025-04-01SHAANXI SCI TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411639336.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-04-01
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

Traditional magnetized mineral materials have problems such as small specific surface area and weak magnetism during the microplastic removal process, which is difficult to meet the selective removal of microplastics in wastewater.

Method used

A porous magnetic composite material with metal oxides loaded with coal gangue as the base is used to form a composite material with strong magnetic and porous structure by anchoring metal ions on the surface and pores of coal gangue.

Benefits of technology

The magnetization strength, specific surface area and pore structure of the material are significantly improved, and the targeted removal ability of microplastics in wastewater is enhanced, and the removal efficiency is several times higher than that of traditional materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140059B_ABST
    Figure CN119140059B_ABST
Patent Text Reader

Abstract

The invention discloses a gangue-based porous magnetic composite material and a preparation method and application thereof, and belongs to the technical field of wastewater treatment. Industrial solid waste gangue has a wide source and low cost. A simple acidification-coprecipitation two-step method is proposed to convert it into a porous magnetic composite material for removing microplastics in wastewater, thereby achieving the purpose of treating waste with waste. The gangue is first acidified to obtain a porous body, and then iron, magnesium and zinc ion solutions and alkaline solutions are added respectively for magnetization treatment to obtain a composite material. The obtained material is based on the porous gangue obtained after acidification, and the metal oxide obtained by coprecipitation is anchored on the surface, which gives the material a high specific surface area and magnetic characteristics, and realizes efficient targeted removal of microplastics in wastewater. The material of the present invention has significantly improved microplastic enrichment efficiency and stability compared with traditional biochar materials, and the adsorption amount of microplastics in domestic wastewater can reach more than 90 mg / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of wastewater treatment, and in particular to a gangue-based porous magnetic composite material for removing microplastics in wastewater and a preparation method thereof. Background Art

[0002] Microplastics have become a new type of pollutant that is difficult to treat in current wastewater treatment due to their easy accumulation in the environment, difficulty in degradation, and strong adsorption of organic pollutants and heavy metals. They are also very easy to escape from sewage treatment barriers into the water environment due to their small size advantage. Magnetized mineral materials are metal oxide materials with large pore volume and strong magnetism. Metal oxide particles self-assemble on their surface to form a porous structure, which gives them excellent properties such as strong magnetism and stable chemical properties. In particular, due to their rich pore structure and strong magnetism, they can achieve targeted identification and removal of microplastics in water bodies, greatly improving the purification efficiency of microplastics in wastewater. Their performance in removing microplastics is significantly better than that of traditional carbon materials and metal oxides. They are currently rare magnetized mineral materials that can efficiently remove microplastics in actual wastewater. However, traditional magnetized mineral materials are metal oxides self-assembled by metal ions, with high source material costs and difficult to prepare on a large scale. By using industrial solid waste coal gangue as the substrate and through means such as micro-interface structure regulation and modification, its physical properties (pore volume, surface roughness and pore structure, etc.) and magnetic intensity can be significantly improved, thereby producing a composite material with porous coal gangue as the substrate and strong magnetism. The obtained material has great application prospects in the field of microplastic treatment in wastewater.

[0003] Traditional mineral materials have problems such as small specific surface area and weak magnetism in the process of removing microplastics, which makes it difficult to meet the requirements of selective removal of microplastics in wastewater. Using coal gangue as a substrate to load metal oxides can improve the magnetization intensity, specific surface area and pore structure of the material to meet the requirements of targeted removal of microplastics in wastewater. Therefore, the present invention proposes a technology suitable for loading metal oxides on coal gangue, which anchors metal ions on the surface of coal gangue to obtain a coal gangue-based porous magnetic composite material with integrated porosity and strong magnetic function. Summary of the invention

[0004] The purpose of the present invention is to provide a gangue-based porous magnetic composite material and a preparation method thereof to meet the treatment needs of removing microplastics in water bodies such as domestic sewage and industrial wastewater.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0006] A gangue-based porous magnetic composite material for removing microplastics in wastewater and a preparation method thereof, comprising the following steps:

[0007] (1) Using coal gangue particles as a substrate, immersing them in an acidified liquid for 1 to 12 hours (preferably 2 to 8 hours), and then mechanically stirring them for 3 to 12 hours (preferably 6 to 12 hours), washing the material with water until the pH value of the waste liquid after washing is neutral, and then drying the coal gangue in an oven at 50 to 80°C (preferably 50 to 65°C) for 2 to 6 hours (preferably 3 to 6 hours) to obtain acidified coal gangue;

[0008] (2) Surface ionization: prepare a metal ion reagent A, uniformly mix the acidified coal gangue obtained above and the metal ion reagent A, and mechanically stir for 1 to 6 hours (preferably 3 to 6 hours) to obtain a metal ion-modified coal gangue solid-liquid mixture; the reagent A is an aqueous solution of ferric chloride, magnesium chloride or zinc chloride;

[0009] (3) Surface magnetization: slowly adding an alkali reagent B to the metal ion modified coal gangue solid-liquid mixture for co-precipitation, and when the pH value of the solution is 9 to 11 (preferably 9 to 10), a metal oxide modified coal gangue solid-liquid mixture is obtained; the alkali reagent B is a sodium carbonate or sodium bicarbonate solution;

[0010] (4) The mixture prepared in step (3) is placed in a 60±5°C water bath, and the temperature is gradually raised to 95±5°C. After maintaining the temperature for a certain period of time, the sample is filtered, washed, and dried to obtain a coal gangue-based porous magnetic composite material.

[0011] In step (1), the acidifying solution is nitric acid or oxalic acid solution, with a mass fraction of 10-30wt.%;

[0012] In step (1), the mass ratio of coal gangue particles to acidizing solution is 1:(15-30).

[0013] In step (2), the preparation method of the metal ion reagent A is: pouring ferric chloride, magnesium chloride or zinc chloride powder into water, mechanically stirring for 10 to 30 minutes until the powder is completely dissolved, to obtain ferric chloride, magnesium chloride or zinc chloride solution; wherein the mass fraction of the ferric chloride, magnesium chloride or zinc chloride aqueous solution reagent is 1 to 5wt.%;

[0014] In step (2), the mass ratio of acidified coal gangue to metal ion reagent A is 1:(5-12)

[0015] In step (3), the preparation method of the alkaline reagent B is: pouring sodium carbonate or sodium bicarbonate powder into water, mechanically stirring for 10 to 30 minutes until it is completely dissolved, to obtain an alkaline solution of sodium carbonate and sodium bicarbonate; wherein the mass fraction of the sodium carbonate or sodium bicarbonate aqueous solution is 2 to 10 wt.%;

[0016] In step (5), the temperature rise process is as follows: from 60±5°C, the temperature is raised at 5~10°C / min to 80±5°C, and the temperature is kept at that temperature for 2~3h; then the temperature is raised at 5~10°C / min to 95±5°C, and the temperature is kept at that temperature for 1~3h.

[0017] Step (2) and step (3) can be performed once or repeatedly. The types and concentrations of the metal ion reagent A and the alkali reagent B, the order of the steps, and the resulting materials are as follows:

[0018] 1) Performing once: 1~5wt.% ferric chloride surface ionization, 3~8wt.% sodium carbonate surface magnetization; the obtained composite material is ferroferric oxide modified porous coal gangue;

[0019] 2) Performing once: 2~5wt.% magnesium chloride surface ionization, 3~6wt.% sodium bicarbonate surface magnetization; the obtained composite material is magnesium oxide modified porous coal gangue;

[0020] 3) Performing once: 3~5wt.% zinc chloride surface ionization, 5~10wt.% sodium bicarbonate surface magnetization; the obtained composite material is zinc oxide modified porous coal gangue;

[0021] 4) Performing the process twice: first, 1-3wt.% ferric chloride surface ionization, 3-8wt.% sodium bicarbonate surface magnetization; second, 2-4wt.% magnesium chloride surface ionization, 3-6wt.% sodium bicarbonate surface magnetization; the obtained composite material is ferroferric oxide-magnesium oxide modified porous coal gangue;

[0022] 5) Performing the process twice: first, 1-3wt.% ferric chloride surface ionization, 3-8wt.% sodium bicarbonate surface magnetization; second, 2-4wt.% zinc chloride surface ionization, 5-10wt.% sodium bicarbonate surface magnetization; the obtained composite material is ferroferric oxide-zinc oxide modified porous coal gangue;

[0023] 6) The process is performed three times: the first time, 1~3wt.% ferric chloride is surface ionized, and 3~8wt.% sodium bicarbonate is surface magnetized; the second time, 1~3wt.% magnesium chloride is surface ionized, and 3~6wt.% sodium bicarbonate is surface magnetized; the third time, 1~2wt.% zinc chloride is surface ionized, and 5~10wt.% sodium bicarbonate is surface magnetized; the obtained composite material is ferroferric oxide-magnesium oxide-zinc oxide modified porous coal gangue.

[0024] The gangue-based porous magnetic composite material prepared by the above method is composed of a porous gangue substrate and a metal oxide anchored on the surface, wherein the oxide is ferroferric oxide or zinc oxide or magnesium oxide or ferroferric oxide-magnesium oxide or ferroferric oxide-zinc oxide or ferroferric oxide-magnesium oxide-zinc oxide.

[0025] The gangue-based porous magnetic composite material has a strong adsorption effect on new pollutants such as microplastics, and can achieve efficient purification of domestic sewage and industrial wastewater.

[0026] The design mechanism of the present invention is as follows:

[0027] With coal gangue as the source material, acid reagents of different concentrations and types are used to destroy the crystal structure of coal gangue to increase the porosity; metal salt reagents of different concentrations are used to anchor metal ions on the surface and inside the pores of acidified coal gangue to provide active sites for the controllable construction of metal oxides; then alkaline solutions of different types and concentrations are used to co-precipitate with the metal ion-anchored coal gangue material to form metal oxides, and the obtained coal gangue composite material has strong magnetism and porous structure. The coal gangue selected in the present invention has a wide source, low price and easy modification, and the obtained coal gangue-based porous magnetic composite material can target and identify microplastics in wastewater and improve the removal performance of microplastics in wastewater.

[0028] The present invention has the following beneficial effects:

[0029] The method of the present invention can achieve the regulation of pore structure and magnetization performance by regulating the type and concentration of acid solution, metal ion type and alkaline solution type and concentration. The specific surface area and magnetization intensity of the material of the present invention are significantly improved compared with traditional mineral materials and magnetized biochar. The specific surface area ranges from 1 to 10 cm 2 / g increased to 80~120cm 2 / g, the magnetization intensity increased from 0.1~5emu / g to 60~118emu / g, and the removal efficiency of microplastics increased from 2~20mg / g to 90~120mg / g. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a diagram of the process preparation of the embodiment described in the present invention.

[0031] Figure 2 Microscopic morphology of coal gangue (a) and ferroferric oxide modified porous coal gangue composite material (b).

[0032] Figure 3 This is the pore diameter distribution diagram of the porous coal gangue composite material modified by ferroferric oxide.

[0033] Figure 4 This is the microscopic morphology structure diagram of the porous coal gangue composite material modified by ferroferric oxide.

[0034] Figure 5 These are the magnetization curves of coal gangue, porous coal gangue composite material modified by ferroferric oxide, and porous coal gangue composite material modified by magnesium oxide.

[0035] Figure 6The adsorption (a) and desorption (b) of spherical microplastics by ferroferric oxide-modified porous coal gangue composite materials.

[0036] Figure 7 This is the microscopic morphology structure diagram of magnesium oxide modified porous coal gangue composite material. DETAILED DESCRIPTION

[0037] In order to understand the present invention in more detail, the present invention is disclosed and explained in conjunction with examples below. However, the examples are only for further elaboration of the features and advantages of the present invention, rather than for limitation of the claims of the present invention.

[0038] Gangue is widely used in environmental governance due to its wide sources and low prices. The main components of gangue produced during lignite mining are 50~65wt.%SiO2, 15~35wt.%Al2O3, 2~8wt.%Fe2O3, and 0.2~2.5wt.%CaO. In this embodiment, the gangue components used are 60.1wt.%SiO2, 33.8wt.%Al2O3, 3.15wt.%Fe2O3, 1.29wt.%CaO, and 1.66wt.% impurities (the data are measured by X-ray fluorescence spectrometer, Shimadzu, Japan). Therefore, the following uses gangue as a source material to prepare a gangue-based porous magnetic composite material by acidification-coprecipitation method as an example to further illustrate the present invention in order to better understand the present invention. Figure 1 It is a process flow chart, but the protection scope of the present invention is not limited to the embodiments.

[0039] Example 1

[0040] The gangue produced in the lignite production process was used as the substrate and passed through a 100-mesh sieve for later use. 5 g of gangue and 100 g of a nitric acid solution with a mass fraction of 20 wt.% were weighed respectively, the gangue was immersed in the nitric acid solution for 2 h and then mechanically stirred for 6 h, then the material was washed with distilled water until the pH value of the waste liquid was neutral, and the gangue was placed in an oven at 60 ° C for 2 h to obtain acidified gangue.

[0041] Weigh 1 g of ferric chloride powder and pour it into 49 g of distilled water, and stir mechanically for 20 min until the powder is completely dissolved to obtain a ferric chloride solution with a mass fraction of 2 wt.%; weigh 5 g of acidified coal gangue and mix it evenly with the above-mentioned metal ion reagent solution, and then stir mechanically for 3 h to obtain an iron ion-modified coal gangue solid-liquid mixture.

[0042] Weigh 5g of sodium carbonate powder and pour it into 95g of distilled water and stir it mechanically for 20min until it is completely dissolved to obtain a sodium carbonate solution with a mass fraction of 5wt.%. Use a rubber dropper to slowly add the sodium carbonate solution to the iron ion-modified coal gangue solid-liquid mixture, use a pH meter to measure the pH value of the solution at any time, and stop adding the sodium carbonate solution when the pH is 10.

[0043] The obtained mixture was placed in a 60°C water bath, heated to 80°C at 10°C / min, kept warm for 2 hours, and then heated to 100°C at 6°C / min, and kept warm for 2 hours; the sample was filtered and washed with distilled water, and dried at 50°C for 4 hours to obtain ferrosoferric oxide modified porous coal gangue.

[0044] The contents of the components in the obtained material are 21.3wt.% SiO2, 14.7wt.% Al2O3, 4.53wt.% Fe2O3, 59.4wt.% Fe3O4, and 0.07wt.% impurities, respectively. Compared with the untreated gangue material, the porosity is increased from 10% to 60%, and the specific surface area is increased from 5.16cm 2 / g increased to 87.9cm 2 / g (the data was measured by BSD-660S series specific surface area and pore size analyzer, Beijing Best Instruments), the magnetization intensity increased from 0.15emu / g to 105emu / g (the data was measured by VSM-100 vibrating sample magnetometer, Changchun Yingpu Magnetoelectric Technology Development Company), and the removal efficiency of microplastics increased from 2.45mg / g to 93.6mg / g (the data was measured by X-ray fluorescence spectroscopy, China Thermo Fisher). At the same time, the material has good adsorption stability for the adsorbed microplastics, and the desorption amount is only 2.3%. Figure 2 The microscopic morphology structure diagram of the composite material of coal gangue and ferroferric oxide modified porous coal gangue in the present invention. It can be found that the coal gangue exhibits a cubic structure with a smooth surface, while the surface of the modified composite material is loose and porous, and the roughness is increased. Figure 3 The pore diameter and pore area distribution diagram of the composite material of coal gangue and ferroferric oxide modified porous coal gangue of the present invention shows that the pore diameter of the modified coal gangue increases from 3.24-42.1 nm to 5.22-55.8 nm, and the specific surface area increases from 5.16 cm 2 / g increased to 87.9cm 2 / g, indicating that the pore diameter and specific surface area of ​​the modified material are increased. Figure 4 This is the microscopic morphology structure diagram of spherical microplastics adsorbed on ferroferric oxide modified porous coal gangue. It can be found that a large number of spherical microplastic particles are adsorbed on the surface of ferroferric oxide modified porous coal gangue composite materials, and the solid particles adhered to the surface of microplastics can improve the agglomeration properties of microplastics. Figure 5 This is the magnetization curve of the ferroferric oxide modified porous coal gangue composite material. It can be found that the magnetization intensity of the obtained material increases from 0.15emu / g to 105emu / g, which can enhance the targeted identification and fixation of microplastics in wastewater. Figure 6(a) is a comparison of the adsorption capacity of spherical microplastics by coal gangue, magnetic biochar and ferroferric oxide-modified porous coal gangue composites. It can be found that the removal efficiency of the obtained material for spherical microplastics is stronger than that of the comparison material. Figure 6 (b) Adsorption and desorption of spherical microplastics by porous gangue composite material modified by ferroferric oxide. It can be found that the adsorption stability rate of the obtained material for microplastics in wastewater is maintained at more than 94%.

[0045] Example 2

[0046] The gangue produced in the lignite production process was used as the substrate and passed through a 100-mesh sieve for later use. 5 g of gangue and 75 g of a 30 wt.% nitric acid solution were weighed respectively, the gangue was immersed in the nitric acid solution for 2 h and then mechanically stirred for 8 h, then the material was washed with distilled water until the pH value of the waste liquid was neutral, and the gangue was placed in an oven at 50 ° C for 5 h to obtain acidified gangue.

[0047] Weigh 1 g of magnesium chloride powder and pour it into 39 g of distilled water, mechanically stir for 10 min until the powder is completely dissolved to obtain a solution with a mass fraction of 2.5 wt.%; weigh 5 g of acidified coal gangue and mix it evenly with the above solution, then mechanically stir for 1 h to obtain a magnesium ion modified coal gangue solid-liquid mixture.

[0048] Weigh 5g of sodium bicarbonate powder and pour it into 95g of distilled water and stir it mechanically for 20min until it is completely dissolved to obtain a solution with a mass fraction of 5wt.%. Use a rubber-tipped dropper to slowly add the sodium bicarbonate solution to the solid-liquid mixture of coal gangue modified with magnesium ions, use a pH meter to measure the pH value of the solution at any time, and stop adding the sodium bicarbonate solution when the pH is 9.

[0049] The obtained mixture was placed in a 60°C water bath, heated to 75°C at 5°C / min, kept warm for 2 hours, and then heated to 95°C at 5°C / min, and kept warm for 3 hours; the sample was filtered and washed with distilled water, and dried at 50°C for 4 hours to obtain magnesium oxide-modified porous coal gangue.

[0050] The contents of the components in the obtained material are 32.9wt.% SiO2, 21.7wt.% Al2O35.76wt.% Fe2O3, 39.6wt.% MgO, and 0.04wt.% impurities, respectively. Compared with the untreated gangue material, the porosity is increased from 10% to 65%, and the specific surface area is increased from 5.16cm 2 / g increased to 92.5cm 2 / g, the magnetization intensity increased from 0.15emu / g to 110emu / g, and the removal efficiency of microplastics increased from 2.45mg / g to 91.8mg / g. Figure 5This is the magnetization curve of the magnesium oxide modified porous coal gangue composite material. It can be found that the magnetization intensity of the modified material has significant characteristics and increases to 110emu / g, indicating that the obtained material has strong magnetic properties. Figure 7 This is the microstructural morphology of the magnesium oxide modified porous coal gangue composite material. It can be found that the surface of the obtained material is rough, loose and porous, and there are a large number of particles anchored.

[0051] Example 3

[0052] The gangue produced in the process of lignite production was used as the substrate and passed through a 100-mesh sieve for later use. 5 g of gangue and 90 g of 25 wt.% oxalic acid solution were weighed respectively, the gangue was immersed in the oxalic acid solution for 8 h and then mechanically stirred for 10 h, then the material was washed with distilled water until the pH value of the waste liquid was neutral, and the gangue was placed in an oven at 55 ° C for 4 h to obtain acidified gangue.

[0053] Weigh 2.5 g of zinc chloride powder and pour it into 47.5 g of distilled water, and stir mechanically for 15 minutes until the powder is completely dissolved to obtain a solution with a mass fraction of 5 wt.%; weigh 5 g of acidified coal gangue and mix it evenly with the above solution, and then stir mechanically for 6 hours to obtain a zinc ion-modified coal gangue solid-liquid mixture.

[0054] Weigh 8g of sodium bicarbonate powder and pour it into 92g of distilled water and stir it mechanically for 20min until it is completely dissolved to obtain a solution with a mass fraction of 8wt.%. Use a rubber-tipped dropper to slowly add the sodium bicarbonate solution to the zinc ion-modified coal gangue solid-liquid mixture, use a pH meter to measure the pH value of the solution at any time, and stop adding the sodium bicarbonate solution when the pH is 9.

[0055] The obtained mixture was placed in a 65°C water bath, heated to 80°C at 5°C / min, kept warm for 3 hours, and then heated to 100°C at 8°C / min, and kept warm for 2 hours; the sample was filtered and washed with distilled water, and dried at 50°C for 4 hours to obtain zinc oxide-modified porous coal gangue.

[0056] The contents of the components in the obtained material are 34.7wt.% SiO2, 19.6wt.% Al2O34.05wt.% Fe2O3, 41.2wt.% ZnO, and 0.45wt.% impurities, respectively. Compared with the untreated gangue material, the porosity is increased from 10% to 62%, and the specific surface area is increased from 5.16cm 2 / g increased to 95.6cm 2 / g, the magnetization intensity increased from 0.15emu / g to 98.3emu / g, and the removal efficiency of microplastics increased from 2.45mg / g to 94.4mg / g.

[0057] Example 4

[0058] The gangue produced in the process of lignite production was used as the substrate and passed through a 100-mesh sieve for later use. 5 g of gangue and 90 g of 10 wt.% oxalic acid solution were weighed respectively, the gangue was immersed in the oxalic acid solution for 1 hour and then mechanically stirred for 3 hours, then the material was washed with distilled water until the pH value of the waste liquid was neutral, and the gangue was placed in an oven at 50°C and dried for 6 hours to obtain acidified gangue.

[0059] Weigh 1 g of ferric chloride powder and pour it into 49 g of distilled water, and mechanically stir it for 15 minutes until the powder is completely dissolved to obtain a solution with a mass fraction of 2 wt.%; weigh 5 g of acidified coal gangue and mix it evenly with the above solution, and then mechanically stir it for 4 hours to obtain a solid-liquid mixture X containing iron ions.

[0060] Weigh 8g of sodium bicarbonate powder and pour it into 92g of distilled water, stir it mechanically for 20min until it is completely dissolved, and obtain a solution with a mass fraction of 8wt.%. Use a rubber dropper to slowly add the sodium bicarbonate solution to the solid-liquid mixture X, use a pH meter to measure the pH value of the solution at any time, and stop adding the sodium bicarbonate solution when the pH is 10 to obtain a solid-liquid mixture Y containing ferrosoferric oxide.

[0061] 1 g of magnesium chloride powder was weighed and poured into 49 g of distilled water, and mechanically stirred for 15 min until the powder was completely dissolved to obtain a solution with a mass fraction of 2 wt.%; the mixture Y was uniformly mixed with the above solution, and then mechanically stirred for 4 h to obtain a solid-liquid mixture Z containing magnesium ions and ferrosoferric oxide.

[0062] Weigh 6 g of sodium bicarbonate powder and pour it into 94 g of distilled water, stir it mechanically for 20 min until it is completely dissolved, and obtain a solution with a mass fraction of 6 wt.%. Use a rubber dropper to slowly add the sodium bicarbonate solution to the solid-liquid mixture Z, use a pH meter to measure the pH value of the solution at any time, and stop adding the sodium bicarbonate solution when the pH is 10.

[0063] The obtained mixture was placed in a 60°C water bath, heated to 80°C at 5°C / min, kept warm for 3 hours, and then heated to 100°C at 8°C / min, and kept warm for 2 hours; the sample was filtered and washed with distilled water, and dried at 50°C for 4 hours to obtain ferroferric oxide-magnesium oxide modified porous coal gangue.

[0064] The contents of the components in the obtained material are 18.4wt.% SiO2, 14.3wt.% Al2O3, 3.47wt.% Fe2O3, 37.1wt.% Fe3O4, 26.7wt.% MgO, and 0.03wt.% impurities, respectively. Compared with the untreated gangue material, the porosity is increased from 10% to 73%, and the specific surface area is increased from 5.16cm 2 / g increased to 102.2cm 2 / g, the magnetization intensity increased from 0.15emu / g to 101.3emu / g, and the removal efficiency of microplastics increased from 2.45mg / g to 105.4mg / g.

[0065] Example 5

[0066] The gangue produced in the process of lignite production was used as the substrate and passed through a 100-mesh sieve for later use. 5 g of gangue and 150 g of 25 wt.% oxalic acid solution were weighed respectively, the gangue was immersed in the oxalic acid solution for 8 h and then mechanically stirred for 10 h, then the material was washed with distilled water until the pH value of the waste liquid was neutral, and the gangue was placed in an oven at 80 ° C for 2 h to obtain acidified gangue.

[0067] Weigh 1 g of ferric chloride powder and pour it into 49 g of distilled water. Mechanically stir for 15 min until the powder is completely dissolved to obtain a solution with a mass fraction of 2 wt.%. Weigh 5 g of acidified coal gangue and mix it evenly with the above solution. Then mechanically stir for 4 h to obtain a solid-liquid mixture X´ containing iron ions.

[0068] Weigh 10g of sodium bicarbonate powder and pour it into 90g of distilled water, stir it mechanically for 20min until it is completely dissolved, and obtain a solution with a mass fraction of 8wt.%. Use a rubber-tipped dropper to slowly add the sodium bicarbonate solution to the solid-liquid mixture X', use a pH meter to measure the pH value of the solution at any time, and stop adding the sodium bicarbonate solution when the pH is 10 to obtain a solid-liquid mixture Y' containing ferrosoferric oxide.

[0069] Weigh 2 g of zinc chloride powder and pour it into 48 g of distilled water. Mechanically stir for 30 min until the powder is completely dissolved to obtain a solution with a mass fraction of 4 wt.%. Mix the mixture Y´ with the above solution evenly, and then mechanically stir for 4 h to obtain a solid-liquid mixture Z´ containing zinc ions and ferrosoferric oxide.

[0070] Weigh 8g of sodium bicarbonate powder and pour it into 92g of distilled water, stir it mechanically for 20min until it is completely dissolved, and obtain a solution with a mass fraction of 8wt.%. Use a rubber-tipped dropper to slowly add the sodium bicarbonate solution to the solid-liquid mixture Z´, use a pH meter to measure the pH value of the solution at any time, and stop adding the sodium bicarbonate solution when the pH reaches 11.

[0071] The obtained mixture was placed in a 55°C water bath, heated to 80°C at 5°C / min, kept warm for 2 hours, and then heated to 100°C at 7°C / min, and kept warm for 2 hours; the sample was filtered and washed with distilled water, and dried at 50°C for 4 hours to obtain ferroferric oxide-zinc oxide modified porous coal gangue.

[0072] The contents of the components in the obtained material are 19.5wt.% SiO2, 17.8wt.% Al2O34.11wt.% Fe2O3, 35.4wt.% Fe3O4, 23.1wt.% ZnO, and 0.09wt.% impurities, respectively. Compared with the untreated gangue material, the porosity is increased from 10% to 62%, and the specific surface area is increased from 5.16cm 2 / g increased to 88.4cm 2 / g, the magnetization intensity increased from 0.15emu / g to 108.2emu / g, and the removal efficiency of microplastics increased from 2.45mg / g to 106.1mg / g.

[0073] Example 6

[0074] The gangue produced in the process of lignite production was used as the substrate and passed through a 100-mesh sieve for later use. 5 g of gangue and 90 g of 25 wt.% oxalic acid solution were weighed respectively, the gangue was immersed in the oxalic acid solution for 12 h and then mechanically stirred for 12 h, then the material was washed with distilled water until the pH value of the waste liquid was neutral, and the gangue was placed in an oven at 55 ° C for 4 h to obtain acidified gangue.

[0075] Weigh 0.5 g of ferric chloride powder and pour it into 24.5 g of distilled water, and stir it mechanically for 15 min until the powder is completely dissolved to obtain a solution with a mass fraction of 2 wt.%; weigh 5 g of acidified coal gangue and mix it evenly with the above solution, and then stir it mechanically for 4 h to obtain a solid-liquid mixture X" containing iron ions.

[0076] Weigh 8g of sodium bicarbonate powder and pour it into 92g of distilled water, stir it mechanically for 20min until it is completely dissolved, and obtain a solution with a mass fraction of 8wt.%. Use a rubber-tipped dropper to slowly add the sodium bicarbonate solution to the solid-liquid mixture X", use a pH meter to measure the pH value of the solution at any time, and stop adding the sodium bicarbonate solution when the pH is 10 to obtain a solid-liquid mixture Y" containing ferrosoferric oxide.

[0077] 1.2 g of magnesium chloride powder was weighed and poured into 58.8 g of distilled water, and mechanically stirred for 15 min until the powder was completely dissolved to obtain a solution with a mass fraction of 2 wt.%; the mixture Y" was uniformly mixed with the above solution, and then mechanically stirred for 4 h to obtain a solid-liquid mixture Z" containing magnesium ions and ferrosoferric oxide.

[0078] Weigh 6g of sodium bicarbonate powder and pour it into 94g of distilled water, stir it mechanically for 20min until it is completely dissolved, and obtain a solution with a mass fraction of 6wt.%. Use a rubber-tipped dropper to slowly add the sodium bicarbonate solution to the solid-liquid mixture Z", use a pH meter to measure the pH value of the solution at any time, and stop adding the sodium bicarbonate solution when the pH is 10 to obtain a solid-liquid mixture M" containing magnesium oxide and ferrosoferric oxide.

[0079] 0.75 g of zinc chloride powder was weighed and poured into 49.25 g of distilled water, and mechanically stirred for 10 min until the powder was completely dissolved to obtain a solution with a mass fraction of 1.5 wt.%; the mixture M" was uniformly mixed with the above solution, and then mechanically stirred for 4 h to obtain a solid-liquid mixture N" containing zinc ions, magnesium oxide and ferrosoferric oxide.

[0080] Weigh 5g of sodium bicarbonate powder and pour it into 95g of distilled water, stir it mechanically for 20min until it is completely dissolved, and obtain a solution with a mass fraction of 5wt.%. Use a rubber dropper to slowly add the sodium bicarbonate solution to the solid-liquid mixture N", use a pH meter to measure the pH value of the solution at any time, and stop adding the sodium bicarbonate solution when the pH is 9.

[0081] The obtained mixture was placed in a 60°C water bath, heated to 80°C at 6°C / min, kept warm for 3 hours, and then heated to 100°C at 8°C / min, and kept warm for 2 hours; the sample was filtered and washed with distilled water, and dried at 50°C for 4 hours to obtain ferroferric oxide-magnesium oxide-zinc oxide modified porous coal gangue.

[0082] The contents of the components in the obtained material are 17.1wt.% SiO2, 15.3wt.% Al2O3, 3.48wt.% Fe2O3, 25.7wt.% Fe3O4, 19.6wt.% MgO, 18.8wt.% ZnO, and 0.02wt.% impurities, respectively. Compared with the untreated gangue material, the porosity is increased from 10% to 67%, and the specific surface area is increased from 5.16cm 2 / g increased to 112.4cm 2 / g, the magnetization intensity increased from 0.15emu / g to 110.6emu / g, and the removal efficiency of microplastics increased from 2.45mg / g to 114.3mg / g.

[0083] Comparative Example 1:

[0084] Acidified modified coal gangue material: The coal gangue produced in the lignite production process is used as the base, and it is sieved through a 100-mesh sieve for later use. Weigh 5g of coal gangue and 100g of nitric acid solution with a mass fraction of 20wt.%, immerse the coal gangue in the nitric acid solution for 2h, and then mechanically stir for 6h, then use distilled water to wash the material until the pH value of the waste liquid is neutral, and place the coal gangue in an oven at 60℃ for 2h to obtain acidified coal gangue. Weigh 2g of ferric chloride powder and pour it into 48g of distilled water, mechanically stir for 10min until the powder is completely dissolved, and obtain a solution with a mass fraction of 2wt.%; weigh 5g of acidified coal gangue and mix it evenly with the above solution, and then mechanically stir for 3h to obtain an iron ion modified coal gangue solid-liquid mixture. The obtained mixture was placed in a 60℃ water bath, heated to 80℃ at 10℃ / min, kept warm for 2h, and then heated to 100℃ at 6℃ / min, kept warm for 2h; the sample was filtered, washed, and dried to obtain iron ion modified porous coal gangue. The results showed that compared with the untreated coal gangue, the porosity of the material increased from 10% to 55%, and the specific surface area increased from 5.16cm 2 / g increased to 89.4cm 2 / g, but the magnetization intensity only increased from 0.15emu / g to 3.12emu / g, and the amount of microplastics removed was only 20.3mg / g. The magnetization intensity of the ferroferric oxide modified porous coal gangue composite material prepared in Example 1 was greater than that of the material obtained by acidification modification only, and the removal efficiency of microplastics was better.

[0085] Comparative Example 2:

[0086] Alkali-modified gangue material: The gangue produced in the lignite production process is used as the substrate, and it is sieved through a 100-mesh sieve for later use. Weigh 1g of ferric chloride powder and pour it into 49g of distilled water, stir mechanically for 20 minutes until the powder is completely dissolved, and obtain a solution with a mass fraction of 2wt.%; weigh 5g of gangue and mix it evenly with the above solution, and then stir mechanically for 3 hours to obtain an iron ion-modified gangue solid-liquid mixture. Weigh 5g of sodium carbonate powder and pour it into 95g of distilled water and stir mechanically for 20 minutes until it is completely dissolved to obtain a solution with a mass fraction of 5wt.%. Use a rubber-tipped dropper to slowly add the sodium carbonate solution to the iron ion-modified gangue solid-liquid mixture, use a pH meter to measure the pH value of the solution at any time, and stop adding the sodium carbonate solution when the pH is 10. The obtained mixture was placed in a 60℃ water bath, heated to 80℃ at 10℃ / min, kept warm for 2h, and then heated to 100℃ at 6℃ / min, kept warm for 2h; the sample was filtered, washed, and dried to obtain ferroferric oxide modified coal gangue. The results showed that compared with the untreated coal gangue, the porosity of the material was only increased from 10% to 15%, and the specific surface area was only increased from 5.16cm 2 / g increased to 45.7cm 2 / g, the magnetization intensity increased from 0.15emu / g to 58.3emu / g, and the amount of microplastics removed was only 44.5mg / g. The porosity and specific surface area of ​​the porous coal gangue modified by ferroferric oxide prepared in Example 1 were larger than those of the material obtained by alkali modification alone, and the removal efficiency of microplastics was better.

[0087] Comparative Example 3:

[0088] Fly ash as base modified material: The fly ash produced during the combustion of lignite is used as the base, and is sieved through a 100-mesh sieve for later use. Among them, the main components of the selected fly ash are 48.8wt.%SiO2, 44.6wt.%Al2O3, 4.72wt.%Fe2O3, 1.08wt.%CaO, and 0.8wt.% impurities. Weigh 5g of fly ash and 100g of nitric acid solution with a mass fraction of 20wt.% respectively, immerse the fly ash in the nitric acid solution for 2h, and then mechanically stir for 6h, then use distilled water to wash the material until the pH value of the waste liquid is neutral, and place the fly ash in an oven at 60℃ and dry it for 2h to obtain acidified fly ash.

[0089] Weigh 1 g of ferric chloride powder and pour it into 49 g of distilled water, and stir it mechanically for 20 min until the powder is completely dissolved to obtain a solution with a mass fraction of 2 wt.%; weigh 5 g of acidified fly ash and mix it evenly with the above solution, and then stir it mechanically for 3 h to obtain an iron ion modified fly ash solid-liquid mixture.

[0090] Weigh 5g of sodium carbonate powder and pour it into 95g of distilled water, stir it mechanically for 20min until it is completely dissolved, and obtain a solution with a mass fraction of 5wt.%. Use a rubber-tipped dropper to slowly add the sodium carbonate solution to the solid-liquid mixture of fly ash modified with iron ions, and use a pH meter to measure the pH value of the solution at any time. When the pH reaches 10, stop adding the sodium carbonate solution.

[0091] The obtained mixture was placed in a 60°C water bath, heated to 80°C at 10°C / min, kept warm for 2 hours, and then heated to 100°C at 6°C / min, kept warm for 2 hours; the sample was filtered, washed, and dried to obtain ferroferric oxide modified porous fly ash.

[0092] Compared with the untreated fly ash material, the porosity of the obtained material increased from 10% to 56%, and the specific surface area increased from 5.16cm 2 / g increased to 62.5cm 2 / g, the magnetization intensity increased from 0.15emu / g to 56.9emu / g, and the removal efficiency of microplastics increased from 2.45mg / g to 74.2mg / g.

[0093] The porosity, specific surface area and magnetic intensity of the ferroferric oxide modified porous coal gangue prepared in Example 1 are greater than those of the ferroferric oxide modified porous fly ash material, and the removal efficiency of microplastics is better.

[0094] Comparative Example 4:

[0095] Iron-magnesium co-modified gangue material: The gangue produced in the lignite production process is used as the base, and it is sieved through a 100-mesh sieve for later use. Weigh 1g of ferric chloride and 1g of magnesium chloride powder and pour them into 49g of distilled water, stir mechanically for 20 minutes until the powder is completely dissolved, and obtain a mixed solution of ferric chloride and magnesium chloride with a mass fraction of 2wt.%; weigh 5g of gangue and mix them evenly with the above solution, and then stir mechanically for 4 hours to obtain a solid-liquid mixture of iron-magnesium ions modified gangue. Weigh 5g of sodium carbonate powder and pour it into 95g of distilled water and stir mechanically for 20 minutes until it is completely dissolved to obtain a solution with a mass fraction of 5wt.%. Use a rubber-tipped dropper to slowly add the sodium carbonate solution to the solid-liquid mixture of coal gangue modified with iron and magnesium ions, use a pH meter to measure the pH value of the solution at any time, and stop adding the sodium carbonate solution when the pH is 10. The obtained mixture was placed in a 60℃ water bath, heated to 80℃ at 10℃ / min, kept warm for 2h, and then heated to 95℃ at 6℃ / min, kept warm for 2h; the sample was filtered, washed, and dried to obtain ferroferric oxide-magnesium oxide modified coal gangue. The results showed that compared with the untreated coal gangue, the material porosity was only increased from 10% to 18%, and the specific surface area was only increased from 5.16cm 2 / g increased to 55.9cm 2 / g, the magnetization intensity increased from 0.15emu / g to 58.4emu / g, and the amount of microplastics removed was only 52.7mg / g. The porosity and specific surface area of ​​the porous coal gangue modified by ferroferric oxide prepared in Example 1 were larger than those of the material modified by iron and magnesium, and the removal efficiency of microplastics was better.

Claims

1. An application of a coal gangue-based porous magnetic composite material, characterized in that: The gangue produced in the lignite production process is used as a substrate and is sieved through a 100-mesh sieve for later use; 5 g of gangue and 90 g of an oxalic acid solution with a mass fraction of 25 wt.% are weighed respectively, the gangue is immersed in the oxalic acid solution for 12 hours and then mechanically stirred for 12 hours, then the material is washed with distilled water until the pH value of the waste liquid is neutral, and the gangue is placed in an oven at 55°C and dried for 4 hours to obtain acidified gangue; Weigh 0.5 g of ferric chloride powder and pour it into 24.5 g of distilled water, and mechanically stir for 15 min until the powder is completely dissolved to obtain a solution with a mass fraction of 2 wt.%; weigh 5 g of acidified coal gangue and mix it evenly with the above solution, and then mechanically stir for 4 h to obtain a solid-liquid mixture containing iron ions X"; Weigh 8 g of sodium bicarbonate powder, pour it into 92 g of distilled water, and stir it mechanically for 20 min until it is completely dissolved, to obtain a solution with a mass fraction of 8 wt.%; use a rubber dropper to slowly add the sodium bicarbonate solution to the solid-liquid mixture X", use a pH meter to measure the pH value of the solution at any time, and stop adding the sodium bicarbonate solution when the pH is 10, to obtain a solid-liquid mixture Y" containing ferrosoferric oxide; Weigh 1.2 g of magnesium chloride powder and pour it into 58.8 g of distilled water, and mechanically stir for 15 min until the powder is completely dissolved to obtain a solution with a mass fraction of 2 wt.%; uniformly mix the mixture Y" with the above solution, and then mechanically stir for 4 h to obtain a solid-liquid mixture Z" containing magnesium ions and ferrosoferric oxide; Weigh 6 g of sodium bicarbonate powder, pour it into 94 g of distilled water, and stir it mechanically for 20 min until it is completely dissolved to obtain a solution with a mass fraction of 6 wt.%; use a rubber-tipped dropper to slowly add the sodium bicarbonate solution to the solid-liquid mixture Z", use a pH meter to measure the pH value of the solution at any time, and stop adding the sodium bicarbonate solution when the pH is 10 to obtain a solid-liquid mixture M" containing magnesium oxide and ferrosoferric oxide; Weigh 0.75 g of zinc chloride powder and pour it into 49.25 g of distilled water, and mechanically stir for 10 min until the powder is completely dissolved to obtain a solution with a mass fraction of 1.5 wt.%; uniformly mix the mixture M" with the above solution, and then mechanically stir for 4 h to obtain a solid-liquid mixture N" containing zinc ions, magnesium oxide and ferrosoferric oxide; Weigh 5 g of sodium bicarbonate powder and pour it into 95 g of distilled water, stir it mechanically for 20 min until it is completely dissolved, and obtain a solution with a mass fraction of 5 wt.%; use a rubber dropper to slowly add the sodium bicarbonate solution to the solid-liquid mixture N", use a pH meter to measure the pH value of the solution at any time, and stop adding the sodium bicarbonate solution when the pH is 9; The obtained mixture was placed in a 60°C water bath, heated to 80°C at 6°C / min, kept warm for 3 h, then heated to 100°C at 8°C / min, kept warm for 2 h; The sample was filtered and washed with distilled water, and dried at 50°C for 4 h to obtain ferroferric oxide-magnesium oxide-zinc oxide modified porous coal gangue; The contents of each component in the obtained material are 17.1wt.%SiO2, 15.3wt.%Al2O 3、 3.48wt.%Fe2O3, 25.7wt.%Fe3O4, 19.6wt.% MgO, 18.8wt.% ZnO, 0.02wt.% impurities, and the porosity of the untreated gangue material increased from 10% to 67%, and the specific surface area increased from 5.16cm 2 / g increased to 112.4cm 2 / g, the magnetization intensity increased from 0.15emu / g to 110.6emu / g, and the removal efficiency of microplastics increased from 2.45mg / g to 114.3mg / g.

Citation Information

Patent Citations

  • Preparation method of metal modified porous adsorbent for adsorbing microplastics in water body

    CN118616029A